Antibody‐drug conjugates targeting CD248+ myofibroblasts effectively alleviate renal fibrosis in mice. Issue 2 (31st December 2021) - Xu, Chao; Liu, Shaojie; Yang, Fa; Zhang, Keying; Li, Yu; Zhao, Xiaolong; Zhang, Jiayu; Lu, Tong; Lu, Shiqi; Jiang, Yao; Qin, Weijun; Shi, Changhong; et al.
Abstract: Myofibroblasts, or activated fibroblasts, play a critical role in the process of renal fibrosis. Targeting myofibroblasts to inhibit their activation or induce specific cell death has been considered to be an effective strategy to attenuate renal fibrosis. However, specific biomarkers for myofibroblasts are needed to ensure the efficacy of these strategies. Here, we verified that CD248 was mainly expressed in myofibroblasts in patients with chronic kidney disease, which was inversely correlated with renal function. The same result was also confirmed in renal fibrotic mice induced by unilateral ureteral obstruction and aristolochic acid nephropathy. By using an antibody‐drug conjugate (ADC) named IgG78‐DM1, in which maytansinoid (DM1) was linked to a fully human antibody IgG78 through an uncleavable SMCC linker, we demonstrated that it could effectively bind with and kill CD248 + fibroblasts in vitro and alleviate renal fibrosis in mice models. Besides, we confirmed that IgG78‐DM1 had qualified biosafety in vivo. Our results confirmed that CD248 can be used as a specific marker for myofibroblasts, and specific killing of CD248 + myofibroblasts by IgG78‐DM1 has excellent anti‐fibrotic effect in renal fibrotic mice. Our study expanded the application of ADC and provided a novel strategy for the treatment of renal fibrosis.